(untitled) (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2025)
Abstract. Indonesia is a country with high cultural diversity, where the spirit of nationalism grows side by side with respect for diversity. The principle of Bhinneka Tunggal Ika reflects how regional cultures are united in one Indonesian national identity. Constitutionally, Article 32 Paragraph (1) of the 1945 Constitution affirms the state’s commitment to "respect and maintain the cultures that live in society", which indicates that cultural diversity is protected and made an important part of the national identity. This research aims to understand the meaning of nationalism in the context of local beliefs, especially in the community of adherents of the Sunda Budi Daya Belief. This study uses an ethnographic method with data collection through observation and in-depth interviews with key informants, especially in the implementation of the Ngertakeun Bumi ritual. The ritual of Ngertakeun Bumi is a reflection of nationalistic values that are contextualized in the cultural and spiritual practices of the Sundanese Cultivation community. Nationalism, which emphasizes supreme loyalty to the nation-state, is internalized through symbolic meaning and cultural praxis in the ritual. Understanding the Earth is based on Sundanese cultural values, especially the Sundanese Tritangtu philosophy which consists of three main elements: Buana Nyungcung (upper realm/sky), Buana Larang (lower realm/earth), and Buana Pancatengah (middle nature/human). These three elements reflect the balance and harmony between humans, nature, and spirituality—a concept that can also be read through the perspective of Eco-Theology, which is the theological understanding of the sacred relationship between humans and the environment. The triangle symbol in the Sundanese Tritangtu represents the unity and connectedness of the three dimensions, which cannot be separated. This pattern of relationship is a view of life of the Sundanese people that is rooted in the balance between heaven, earth, and humans, and forms the basis of their ecological and religious consciousness in their daily lives. These values are a concrete form of implementation of the motto of Bhinneka Tunggal Ika, as well as proving that the preservation of traditions and ancestral heritage can be a means of strengthening nationalism. The Ngertakeun Bumi ritual also contributes to the recognition of an inclusive and completely independent state for every citizen, especially in terms of freedom of belief. This practice shows the importance of respect for diversity, as well as the importance of maintaining an open and non-discriminatory sense of nationalism in the midst of a pluralistic Indonesian society.